Tuberous sclerosis: Renal angiomyolipoma in association with pulmonary lymphangioleiomyomatosis - (:unkn) unknown (My University, 1998)
Tuberous sclerosis is a multiple system disease, involving the brain, skin, kidneys, heart and other visceral organs. We report a patient with bilateral renal angiomyolipomas, diffuse pulmonary cysts, and skin adenoma sebaceum. Following the discovery of a renal mass 8 years previously, a left nephrectomy was performed, histopathological examination revealing increased kidney fatty tissue. Exertional dyspnea, spontaneous pneumothorax history, and bilateral multiple cystic lesions in computed tomography of thorax were consistent with pulmonary lymphangioleiomyomatosis, an unusual entity known to coexist with tuberous sclerosis. Over the last few years, pulmonary symptoms have worsened and the right kidney has enlarged secondary to angiomyolipomatosis. We want to report this case since it describes an association between pulmonary lymphangjolei myomatosis and renal angiomyomatosis which is not well documented.
Keywords: Adenoma sebaceum; Lymphangioleiomyomatosis; Renal angiomyolipoma; Tuberous sclerosis